2022
DOI: 10.3390/ijerph19159561
|View full text |Cite
|
Sign up to set email alerts
|

How Do Male Football Players Meet Dietary Recommendations? A Systematic Literature Review

Abstract: The aim of this review was to determine whether male football players meet dietary recommendations according to a UEFA expert group statement and to identify priority areas for dietetic intervention, including training periodization and field position. A database search of PubMed, Web of Science, EBSCO and Scopus was performed. To be included within the final review, articles were required to provide a dietary intake assessment of professional and semi-professional football players. A total of 17 studies met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
1
14
0
2
Order By: Relevance
“…Nonetheless, both men and women, on average, were within the National Academy of Medicine’s Acceptable Macronutrient Distribution Range (AMDR), which is defined as “a range of intakes for a particular energy source that is associated with reduced risk of chronic diseases while providing adequate intakes of essential nutrients,” of 10–35% of total energy intake as protein [ 37 ]. Of note, the habitual daily protein intake amounts of the men’s and women’s soccer players observed in the present cohort are in line with previous findings in soccer players [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Nonetheless, both men and women, on average, were within the National Academy of Medicine’s Acceptable Macronutrient Distribution Range (AMDR), which is defined as “a range of intakes for a particular energy source that is associated with reduced risk of chronic diseases while providing adequate intakes of essential nutrients,” of 10–35% of total energy intake as protein [ 37 ]. Of note, the habitual daily protein intake amounts of the men’s and women’s soccer players observed in the present cohort are in line with previous findings in soccer players [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Though a considerable degree of uncertainty surrounds the topic due to limited data, there is no compelling evidence to issue sex-specific dietary recommendations for total daily protein intake, distribution, and quality of protein at present [ 27 , 28 ]. In general, however, the literature suggests that male soccer players may typically consume more protein than female players do [ 29 , 30 ], a pattern likely explained by the fact that muscle mass accretion usually represents a higher priority goal among male athletes [ 53 , 54 ]. Along similar lines, this study demonstrated that total daily protein quantities—expressed in absolute amounts, on a body weight-adjusted basis, and as a proportion of total energy consumption—were all significantly lower in women as compared to men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, discipline-specific nutritional recommendations are necessary [8]. Several studies have been conducted regarding nutritional recommendations for team sports such as football/soccer [9,10] (and the sex-based differences within these disciplines) [11,12] or rugby [13]. Endurance athletes such as triathletes may be most at risk for micronutrient deficiency because of low energy consumption, coupled with longer physical activity duration and increased sweat rate [14].…”
Section: Introductionmentioning
confidence: 99%
“…Training adaptations, reduced recovery time, reduced susceptibility to injury, and improved exercise capacity all depend on an optimal supply of nutrients [2,3]. Elite football teams already recognize the need for appropriate nutritional interventions due to the increasing physiological demands on football players [4,5].…”
Section: Introductionmentioning
confidence: 99%